Implementation of Academic Information System Services Universitas Bumi Persada Using the Webqual 4.0 - Teuku Afriliansyah; Eka Utami Ningsih (Proceeding of International Conference on Multidisciplinary Research, 2024)
The Academic Information System is an academic data processing service such as student data, grade data, teacher data and course data that will be selected by students. the method used in this academic information system uses quantitative research. while the Webqual 4.0 technique is used to measure, evaluate the quality of academic information system services using three dimensions namely usability quality, information quality and also service interaction quality. the results of calculations using multiple linear regression and SPSS R Square applications, while the results of student satisfaction are obtained based on a success rate of 61%, this means that many respondents chose the answer agree. Test variable X (Independent) has an influence or correlation on test variable Y (Dependent). where the t table test value is at 1.83278 which indicates that H1, H2 and H3 can be partially accepted. Partial t test results obtained from the t test with variable values X1, X2, and X3 amounting to (1,989, 3,978, and 4,189) which are stated to have an effect on variable Y.